Actitudes hacia el aprendizaje del fútbol y el baloncesto en estudiantes de Educación Física de la Institución Educativa Pública Nº 60222 Santa María de Fátima, Río Amazonas 2022 - Jarama Donayre, Jhempool Jhery (2024)
The main goal of this research was to compare attitudes towards learning soccer and basketball in physical education students at Public Educational Institution No. 60222 Santa María de Fátima, located in the Amazon River, in 2022. The methodological design was comparative, field-based, and cross-sectional. The study sample included 98 students, and the data collection technique was a survey, applied through a questionnaire. In terms of preference, 58.1% of the students showed a high attitude towards soccer, while none showed a high attitude towards basketball. Additionally, 11.3% of the students had a medium attitude towards soccer, compared to 17.3% towards basketball. On the other hand, 30.6% of the students showed a low attitude towards soccer, compared to 82.7% who showed a low attitude towards basketball. These results show a clear preference and a more favorable attitude towards soccer compared to basketball. The conclusions of this research indicate a strong preference for and more positive attitude of the students towards soccer compared to basketball. Most students have a low attitude towards basketball, highlighting the need to explore the reasons behind this disparity.